SCANNING CALORIMETRIC DETERMINATIONS OF THE HEAT CONTENTS OF DIOPSIDE-RICH SYSTEMS DURING MELTING AND CRYSTALLIZATION - DeYoreo J.J.; Lange R.A.; Navrotsky A. (My University, 1995)
The results of scanning calorimetric measurements on crystalline albite, diopside, diopside-anorthite, and diopside-wollastonite-enstatite are reported in the temperature range of 1300 K to 1775 K. The results for albite agree with those obtained previously using a drop-calorimetric technique and confirm that melting takes place during a 300 K temperature interval starting near the accepted equilibrium melting point of 1373 K. The heat content, H(T), of anorthite-diopside mixtures is calculated numerically based on existing thermodynamic data. The results are compared to measurements on a mechanical mixture of 10 mol% anorthite-90 mol% diopside containing 3% of second phase impurities. Due to the presence of these impurities, the onset of premelting or melting occurs at 150 K below the An-Di eutectic and the heat of fusion at the liquidus (1665 K) is 114 +/- 6 kJ/mol, which is 6% less than calculated for the pure mixture. Measurements of H(T) on a sample of 13 mol% wollastonite-83 mol% diopside are also presented. The measured heat of fusion at 1665 K is 125 +/- 7 kJ/mol, in excellent agreement with the value of 124.8 kJ/mol calculate from existing thermodynamic data. Our data place an upper limit of 7 kJ/mol on the heat of mixing in this system at 1665 K.